Continous use of iodized salt may cause thyrotoxicoses in plain areas of North West Frontier Province (NWFP) of Pakistan - Khan, Alam; Akhter, Shahmim; Siddiqui, M. Mohsin; Nawab, Gul; Khattak, Muzaffar Ali Khan (Ansi Network for Scientiific Information, 2003)
The effect of iodized and uniodized salt on the concentration of thyroid hormones 2(T3and T4) and thyroid stimulating hormone (TSH) was studied in 411 individuals, who were the residents of Peshawar and its vicinity and were referred by physicians to the radio immunoassay (RIA) laboratory of the Institute of Radiotherapy and Nuclear Medicine (IRNUM), Peshawar during 1998 for thyroid hormones tests. Out of these 411 individuals, 148 were using iodized salt and 263 were using uniodized salt. The iodized and uniodized salt users were called experimental and control groups, respectively. Blood samples were taken form both the groups and T3and T4in the blood serum were determined by radio immunoassay (RIA) while TSH was determined by immunoradiometricassay (IRMA). The mean concentration of T3was 2.337 and 2.287 nmol L-1in the experimental and control groups respectively. The mean concentration of T4was 109.415 and 105.918 nmol L-1in the experimental and control groups, respectively. The mean concentration of TSH was 3.99 and 4.55 miu L-1in the experimental and control groups respectively. The result indicated that continuous use of iodized salt increased both T3and T4and decreased TSH in the experimental group which is an indication for thyrotoxicoses. However the increase in T3and decrease in TSH were non significant but the increase in T4was ignificant and at p<0.05 as compared to the control group. The data suggest that long and un-necessary use of iodized salt may produce sub clinical hyperthyroidism and hyrotoxicosis in the plain areas of NWFP. Close monitoring of T3, T4and TSH of individuals, who are using iodized salt, is recommended.